2004
DOI: 10.3138/jcfs.35.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Inter-racial Marriages in South Africa

Abstract: Using the ten percent sample of the 1996 South African census, we examine the rates of intergroup marriage and marriage between linguistic groups in South Africa. Since whites are a small number in South Africa but historically have held most of the power, the analysis provides an interesting context to test the generalizability of theories about inter-racial marriage. We test exchange theory by examining the effects of education on the patterns of intergroup marriage. We do this while controlling for relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…While it was found that the groups vary significantly from each other, the difference between Black and Colored individuals was found to be less than between either of these groups and the White group, as reflected in the Mahalanobis distances between the groups. This is also in agreement with the results of the study by Stull et al (16), as well as historical and genetic studies of these populations (22,23,57,65). It is thus not surprising that the accuracy of ancestry estimation using the detected morphological variation of the cranium resulted in significantly higher accuracies for the White individuals (90.2%) than for the Black and Colored individuals (82.0% and 78.2%, respectively).…”
Section: Ancestrysupporting
confidence: 91%
“…While it was found that the groups vary significantly from each other, the difference between Black and Colored individuals was found to be less than between either of these groups and the White group, as reflected in the Mahalanobis distances between the groups. This is also in agreement with the results of the study by Stull et al (16), as well as historical and genetic studies of these populations (22,23,57,65). It is thus not surprising that the accuracy of ancestry estimation using the detected morphological variation of the cranium resulted in significantly higher accuracies for the White individuals (90.2%) than for the Black and Colored individuals (82.0% and 78.2%, respectively).…”
Section: Ancestrysupporting
confidence: 91%
“…Comparable percentages for other countries suggest that the black-white boundary is stronger elsewhere. In the United States in the 1990s, only 8% of black men is married outside the group (Qian, 1997) and in South Africa, this is even rarer (Jacobson, Amoateng, & Heaton, 2004). In England, about 16-18% of foreign-born black men are married to a native white partner (Model & Fisher, 2002).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…For example, scenarios of preference for or against new migrants compared to other admixed individuals have been hypothesized in swordfish, butterflies, and grasshoppers (R ITCHIE et al ., 1989; H OWARD , 1993; D UENEZ -G UZMAN et al ., 2009; M ELO et al ., 2009; S CHUMER et al ., 2017). Similarly, in admixed human populations, language barriers or social identities may produce population-based preferences (Q IAN , 1997; J ACOBSON et al ., 2004; R UIZ -L INARES et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A particular form of assortative mating by admixture can be more specifically characterized as assortative mating by source population (R ITCHIE et al ., 1989; H OWARD , 1993; D UENEZ -G UZMAN et al ., 2009; M ELO et al ., 2009; R UIZ -L INARES et al ., 2014; S CHUMER et al ., 2017). In this type of assortative mating by admixture, different groups—source populations and admixed populations, for example—come to have distinct geographic locations, trait preferences, host preferences, or in the case of human populations, social identities (Q IAN , 1997; J ACOBSON et al ., 2004). Individual ancestry levels within the admixed group are less important for mating choices than the group membership itself.…”
Section: Introductionmentioning
confidence: 99%